Bedside bilateral sequential intravitreal anti-VEGF injections for retinopathy of prematurity - Priya Bajgai; Susree Satavisa; Taraprasad Das; Subhadra Jalali; Balakrushna Samanataray; Sameera Nayak; Tapas Ranjan Padhi (Indian Journal of Ophthalmology)
Purpose: To evaluate the outcome and ocular adverse events of bedside bilateral sequential intravitreal anti-vascular endothelial growth factor injections for retinopathy of prematurity (ROP) (BBSIR). Methods: This retrospective interventional study included infants who received BBSIR with a follow-up of at least 1 month. Clinical history, intravitreal injection details, indications, intraoperative and postoperative ocular adverse events, and outcomes were analyzed. Results: The study cohort included 192 babies (384 eyes) spread over 9 years. The mean gestational age was 30.2 ± 2.6 weeks (28.8–34.1), and the birth weight was 1098.11 ± 271.65 g (650–2000). The indications for BBSIR were as follows: 73.4% (n = 141 infants) were too sick to transfer to an ophthalmic unit, 10.9% (n = 21 infants) due to the parents’ inconvenience of traveling to the ophthalmic center, and 15. 6% (n = 30 infants) due to both reasons. The injections were given by an ROP specialist/ROP-trained ophthalmologist after due parental consent, considering each eye as a fresh eye with separate scrubbing and draping. Light from the head-worn indirect ophthalmoscope served as the source of illumination. The retinopathy was regressing/regressed in 92.4% of babies until the last follow-up. The major ocular complication was cataract in 2 eyes (0.5%). There was no incidence of endophthalmitis till last follow-up (median 5.7 months). Conclusions: As per this study, BBSIR was observed to be effective and safe if given by those fully trained in the management of ROP. Though the rate of complications like cataract is small, they can pose management challenges and impact vision in a growing child.